A Discourse-Pragmatic Study of Lecturer and Student Conversations in English Literature Course - Ahmad Ridwan; Shafruddin Tajuddin; Eva Leiliyanti (Lafadz Jaya Publisher, 2023)
This study aimed to explain and describe (1) the speech acts used in the conversation between lecturers and students in English Literature Course; and (2) the intentions behind the conversation between lecturers and students in English Literature Course. This study used a qualitative research method. Data collection was analyzed using listening and note-taking techniques. The analysis technique was implemented using the flowing technique. The results of this study can be concluded as follows: (1) lecturers and students used locutionary, illocutionary, and perlocutionary speech acts in learning; (2) the purposes contained behind the lecturers' and students' utterances, among others: to instruct, motivate, clarify, reinforce, entertain, and conclude. Thus, the conversations between lecturers and students used direct and indirect speech acts in English Literature Course.